Short Communication: DNA barcoding reveals vulnerable and not evaluated species of sea cucumbers (Holothuroidea and Stichopodidae) from Kepulauan Seribu reefs, Indonesia - HAWIS MADDUPPA; AM AZBAS TAURUSMAN; BEGINER SUBHAN; NURLITA P ANGGRAINI; RISKI FADILLAH; KUSTIARIYAH TARMAN (Society for Indonesian Biodiversity, 2017)
Madduppa H, Taurusman AA, Subhan B, Anggraini NP, Fadillah R, Tarman K. 2017. DNA barcoding reveals vulnerable and not evaluated species of sea cucumbers (Holothuroidea and Stichopodidae) from Kepulauan Seribu reefs, Indonesia. Biodiversitas 18: 893-898. DNA Barcoding is a tool in the molecular taxonomy which allows a rapid and precise identification. This tool is needed to mitigate difficulties in identifying species of sea cucumbers in Indonesia. This study was conducted to reveal species diversity in sea cucumbers (Holothuridae and Stichopodidae), commonly harvested in the Kepulauan Seribu reefs, northern Jakarta, Indonesia, by using mitochondrial DNA. Neighbor-joining phylogenetic trees were reconstructed using the Kimura-2 parameter with 1000 of bootstrap values. The genetic distance within and between species was investigated. Conservation and trade status of the species were determined using IUCN and CITES, respectively. DNA barcoding using mitochondrial Cytochrome oxidase 1 (COI) revealed 7 species from 96 samples, of which 4 species belonged to the Stichopodidae (Stichopus herrmanni, Stichopus ocellatus, Stichopus horrens, Stichopus monotuberculatus), and 3 species to the Holothuridae (Bohadschia bivittata, Actinopyga lecanora and Holothuria leucospilota). Phylogenetic analysis showed that the two families were separated with a high bootstrap value. The neighbor-joining tree supported the result of identification of the sea cucumber species. The ingroup haplotypes were clustered into four main clades. Stichopus herrmanni and S. ocellatus were identified as closely related, which matches their morphological characteristics. Bohadschia bivittata is the most distinct species from other species due to the formation of a separate clade in the phylogenetic tree. Stichopus. horrens and S. monotuberculatus were also identified as very closely related, which might explain the frequent morphological misidentification of both types. The conservation status determined one of the investigated species was categorized as vulnerable, one as least concern, one as not evaluated, and four species in data deficient. The population trend of S.s herrmanni was recorded to be decreasing, whereas it remained unknown for the other 6 species. Surprisingly, all identified species in this study were not evaluated yet by CITES. This study suggests that a proper field monitoring and the establishment of a valid list of commercial and scientific names for the sea cucumbers harvested in Kepulauan Seribu is necessary. This would be valuable for keeping trade records and managing and conserving the targeted sea cucumber species in the region.